Fundamentos de haber otorgado a la subsanación voluntaria la calidad de eximente de responsabilidad por infracciones administrativas - Villena Zelada, Katia Milagritos (2023)
The present investigation seeks to determine what are the legal grounds for the granting of voluntary correction as exemption from liability, given that the administrative entities, considering that the LPAG does not regulate the scope of the exemption, through its regulations, have set guidelines and exceptions not provided for in the TUO of the LPAG, limiting the application of the exemption despite being a guarantee in favor of the company; thus affecting the rights of the administered as well as being faced with a non-uniform criterion that ends up violating the principle of legality, reasonableness and legal certainty. Now, regarding the dogmatic and jurisprudential development, the following chapters are developed: the sanctioning power, the dministrative infraction, the inspection activity and the responsive regulation policy, voluntary correction as an exemption from liability, regulations and jurisprudence issued by the administrative entities. Finally, it was determined that the legal grounds for the granting of voluntary correction as an exemption are to promote voluntary compliance with the rules and the restoration of legality, which is consistent with a responsive regulation policy that superimposes the preventive-corrective purpose for about the repressive purpose.